P635 Carriage of the HLA-DQA1*05 allele is associated with a high risk of loss of response to infliximab in patients with inflammatory bowel disease. (25th January 2019) - Guardiola, J; Rodriguez Alonso, L; Santacana, E; Padró, A; Serra, K; Padullés, N; Ruiz-Cerulla, A; Gilabert, P; Arajol, C; Ibañez-Sanz, G; Camps, B; Orobitg, J; et al.
Abstract: Background: Loss of response (LOR) to tumour necrosis factor antagonists occurs in up to 50% of patients with inflammatory bowel disease (IBD). Immunogenicity is a common cause of loss of response in patients due to the formation of antibodies directed against the drug. The ability to predict which patients are likely to lose response would allow therapies to be tailored to the patient's characteristics. In a recent study from the PANTS consortium, the HLA-DQA1*05 allele identified patients at increased risk of immunogenicity (Sazonovs A et al . JCC 2018; 12(S1): S009–010). The aim of our work was to know whether carriage of a HLA-DQA1*05 allele is associated with secondary loss of response to infliximab (IFX) in patients with IBD. Methods: This is a retrospective cohort study from a prospectively maintained data base. Patients were included if they had achieved response to IFX. LOR was defined as recurrence or worsening of IBD-related symptoms that required a change or intensification in treatment, hospitalisation or surgery. Independent predictors of LOR were identified using univariate and multi-variable Cox proportional hazard regression. Results: We included 64 patients (44 Crohn's disease, 20 ulcerative colitis) followed up to LOR (50%) or a mean of 56 months. Thirty-one per cent were carriers of an HLA-QA1*05 allele. On univariate analysis, body mass index (BMI) (HR 0.9, 95% CI 0.8–0.9, p = 0.038) and HLA-DQA1*05 carriage (HR 4, 95% IC 1.9–8.1, p < 0.001) were associated with LOR. On multi-variate analysis, after adjusting for immunomodulator use and BMI, only the carriage of an HLA-DQA1*05 allele was associated with LOR (HR 3.5, 95% CI 1.6–7.5, p = 0.002) (image 1). Conclusions: HLA-DQA1*05 carriage is frequent in Spanish IBD population and it is associated with a marked increase in the risk of LOR to IFX. Testing for HLA-DQA1*05 could allow treatment to be tailored according to the risk of LOR.